Nutrient Sensing Systems in Fish: Impact on Food Intake Regulation and Energy Homeostasis - Conde-Sieira, Marta; Soengas, José L. (Frontiers in Neuroscience, 2017)
Evidence obtained in recent years in a few species, especially rainbow trout, supports the presence in fish of nutrient sensing mechanisms. Glucosensing capacity is present in central (hypothalamus and hindbrain) and peripheral (liver, Brockmann bodies (BB, main accumulation of pancreatic endocrine cells in several fish species), and intestine) locations whereas fatty acid sensors seem to be present in hypothalamus, liver and BB. Glucose and fatty acid sensing capacities relate to food intake regulation and metabolism in fish, with hypothalamus as a signalling integratory centre in a way that detection of increased levels of nutrients result in food intake inhibition through changes in the expression of anorexigenic and orexigenic neuropeptides. Moreover, central nutrient sensing modulates functions at peripheral level since they elicit changes in hepatic metabolism as well as in hormone secretion to counter-regulate changes in nutrient levels detected in the CNS. At peripheral level, the direct nutrient detection in liver has a crucial role in homeostatic control of glucose and fatty acid whereas in BB and intestine nutrient sensing is probably involved in regulation of hormone secretion from endocrine cells. In the present review, we summarize the achievements of these topics in fish in recent years